PERKAWINAN NGAMALING SOROH BATU JELANTIK DI DESA GULINGAN KECAMATAN MENGWI KABUPATEN BADUNG (PERSPEKTIF PENDIDIKAN AGAMA HINDU) - Putu Melliani Putriyanti; I Nengah Lestawi; I Wayan Lali Yogantara (Upadhyaya : Jurnal Penelitian Pendidikan, 2020)
Marriage is a noble social institution because it is a Grhastha Dormitory, which is a place to carry out the Dharma. Grhastha has an important meaning in the life of Hindu society. One of the ways of marriage that is carried out by means of singing, especially Soroh Batu Jelantik in Gulingan Village, Mengwi District, Badung Regency. The theory used to analyze the formulation of the problem is: 1). Structural Functionalism Theory. 2). Theory of Religion 3) Symbolic Interactionism Theory. The methods used to collect data are non-participatory observation methods, interviews, literature and documents. The technique of determining the informants used was Purposive Sampling. The collected data were analyzed with data analysis techniques with steps of reduction, data presentation, data drawing conclusions. The research results show 1). The reasons for carrying out the Ngamaling Soroh Batu Jelantik marriage in Gulingan Village are: 1. Carrying out the Tradition. 2. The caste system takes place. 3. The existence of interfaith marriage, and 4. Marriage under age. 2). The wedding procession of the Soroh Batu Jelantik wedding in Gulingan Village are: 1). The initial stage of the implementation of the Soroh Batu Jelantik marriage in Gulingan Village: 1. Mapajati 2. Map behavior 3. Inflammation 2).1. Makala-Kalaan ceremony 2. Widhi-Widhana ceremony. 3. Majuman ceremony. 3) The final stage of the implementation of the Ngamaling Soroh Batu Jelantik marriage in Gulingan Village, namely: 1. Macaru Sang Hyang Semara Ratih. 2. Complete marriage administration. 3). The impacts that exist on a ngamaling marriage are: 1. Psychological impact. 2. Impact on Family. 3. Religious Impact. 4. Social Impact.